Indolethylamine-N-Methyltransferase Inhibits Proliferation and Promotes Apoptosis of Human Prostate Cancer Cells: A Mechanistic Exploration - Jianfeng, Wang; Yutao, Wang; Jianbin, Bi (Frontiers in Cell and Developmental Biology, 2022)
Indolethylamine-N-methyltransferase (INMT) is a methyltransferase downregulated in lung cancer, meningioma, and prostate cancer; however, its role and mechanism in prostate cancer remain unclear. By analyzing The Cancer Genome Atlas (TCGA)-PRAD, we found that the expression of INMT in prostate cancer was lower than that of adjacent non-cancerous prostate tissues and was significantly correlated with lymph node metastasis Gleason score, PSA expression, and survival. Combined with the GSE46602 cohorts for pathway enrichment analysis, we found that INMT was involved in regulating the MAPK, TGFβ, and Wnt signaling pathways. After overexpression of INMT in prostate cancer cell lines 22Rv1 and PC-3, we found an effect of INMT on these tumor signal pathways; overexpression of INMT inhibited the proliferation of prostate cancer cells and promoted apoptosis. Using the ESTIMATE algorithm, we found that with the increase of INMT expression, immune and stromal scores in the tumor microenvironment increased, immune response intensity increased, and tumor purity decreased. The difference in INMT expression affected the proportion of several immune cells. According to PRISM and CTRP2.0, the potential therapeutic agents associated with the INMT expression subgroup in TCGA were predicted. The area under the curve (AUC) values of 26 compounds positively correlated with the expression of INMT, while the AUC values of 14 compounds were negatively correlated with the expression of INMT. These findings suggest that INMT may affect prostate cancer's occurrence, development, and drug sensitivity via various tumor signaling pathways and tumor microenvironments.